Fluidic Nozzle Throats in Solid Rocket Motors - Xie, Kan.; Chen, Xinmin; Li, Junwei; Liu, Yu.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the performance and application of fluidic nozzle throats for solid rocket motors, discussing their flow details and characterization performance, as well as the influence of the particle phase on their performance. It comprehensively covers a range of fluidic nozzle throats in solid rocket motors and is richly illustrated with impressive figures and full-color photographs. It is a valuable resource for students and researchers in the fields of aeronautics, astronautics and related industries wishing to understand the fundamentals and theories of fluidic nozzle throats and engage in fluidic nozzle throat analysis and design.
Introduction -- Steady Characteristics of Gas-Gas Aerodynamic Throat -- The Characteristic Function and Nozzle Efficiency -- The Fluidic Nozzle Throat in Gas-particle Two Phase-flow Conditions -- Secondary Flow TVC for Fluidic-Throat Nozzles -- Gas-liquid Fluidic Throat -- Thrust Modulation Process of Fluidic Throat for Solid Rocket Motors -- Erosion Characters of Fluidic Throat in Solid Rocket Motors -- Nozzle Damping of the Fluidic Nozzle -- System Application Models and Key Technologies.
Keywords: Aerospace engineering; Astronautics; Fluid mechanics; Engines; Machinery; Aerospace Technology and Astronautics; Engineering Fluid Dynamics; Engine Technology; Machinery and Machine Elements